Acute Physiologic Stress and Subsequent Anxiety Among Family Members of ICU Patients. Issue 2 (February 2018) - Beesley, Sarah J.; Hopkins, Ramona O.; Holt-Lunstad, Julianne; Wilson, Emily L.; Butler, Jorie; Kuttler, Kathryn G.; Orme, James; Brown, Samuel M.; Hirshberg, Eliotte L.
Abstract : Objectives: The ICU is a complex and stressful environment and is associated with significant psychologic morbidity for patients and their families. We sought to determine whether salivary cortisol, a physiologic measure of acute stress, was associated with subsequent psychologic distress among family members of ICU patients. Design: This is a prospective, observational study of family members of adult ICU patients. Setting: Adult medical and surgical ICU in a tertiary care center. Subjects: Family members of ICU patients. Interventions: Participants provided five salivary cortisol samples over 24 hours at the time of the patient ICU admission. The primary measure of cortisol was the area under the curve from ground; the secondary measure was the cortisol awakening response. Outcomes were obtained during a 3-month follow-up telephone call. The primary outcome was anxiety, measured by the Hospital Anxiety and Depression Scale-Anxiety. Secondary outcomes included depression and posttraumatic stress disorder. Measurements and Main Results: Among 100 participants, 92 completed follow-up. Twenty-nine participants (32%) reported symptoms of anxiety at 3 months, 15 participants (16%) reported depression symptoms, and 14 participants (15%) reported posttraumatic stress symptoms. In our primary analysis, cortisol level as measured by area under the curve from ground was not significantly associated with anxiety (odds ratio, 0.94; p = 0.70). In our secondary analysis, however, cortisol awakening response was significantly associated with anxiety (odds ratio, 1.08; p = 0.02). Conclusions: Roughly one third of family members experience anxiety after an ICU admission for their loved one, and many family members also experience depression and posttraumatic stress. Cortisol awakening response is associated with anxiety in family members of ICU patients 3 months following the ICU admission. Physiologic measurements of stress among ICU family members may help identify individuals at particular risk of adverse psychologic outcomes. Abstract : Supplemental Digital Content is available in the text.